STRATEGI PENINGKATAN BRAND POSITIONING UNTUK PRODUK DAN JASA: PENYULUHAN BAGI PERKUMPULAN UMKM KOMUNITAS SUKSES BERJAMAAH INDONESIA (KSBI) DI JAKARTA SELATAN - Hiswanti, Hiswanti; Misnan, Misnan; Alamsyah, Alamsyah; Bachtiar, Alfan; Pranawukir, Iswahyu (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This proposal aims to provide counseling to the Indonesian Congregational Success Community MSME Association (KSBI) in South Jakarta to improve the brand positioning of their products and services. Brand positioning is a key factor in business success, especially for MSMEs who want to differentiate themselves in a competitive market. In this proposal, the service team will carry out various activities such as literature studies, counseling, training and individual consultations. Through counseling and training, the service team will provide a basic understanding of brand positioning to KSBI members. The material that will be presented includes understanding the concept of brand positioning, identifying the unique value of products and services, brand communication strategies, and the use of social media to strengthen brand positioning. Apart from that, the service team will also provide individual consultations to KSBI members so that they can receive specific input and recommendations regarding the brand positioning of their products and services. This will help MSMEs to adapt strategies that suit the characteristics of the products and services they offer. The activity schedule for this proposal includes preparation, implementation of counseling and training, as well as individual consultations. Evaluation of service activities will be carried out through participant satisfaction surveys and analysis of changes in MSME marketing strategies. The expected results of this service activity are a better understanding of brand positioning, increasing MSME skills in identifying the unique value of products and services, increasing effective marketing activities, as well as positive changes in brand positioning and consumer perceptions of the MSME products and services involved. The service team hopes that this service activity will provide significant benefits for KSBI members in improving the brand positioning of their products and services, as well as helping MSMEs strengthen their position in the market.